(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Multiconfiguration Dirac-Hartree-Fock (MCDHF) calculations and subsequent Relativistic Configuration Interaction (RCI) calculations have been performed for the 5s\(^2\)5p\(^4\), 5s\(^2\)5p\(^3\)6s and 5s5p\(^5\) configurations of six times ionized cerium using GRASP2018 package. The electron correlation effects, (BI) interaction and Quantum Electrodynamics (QED) effects have been considered in the calculation. Energy levels, oscillator strength and transition probabilities among the transitions of 5s\(^2\)5p\(^4\), 5s5p\(^5\) and 5s\(^2\)5p\(^3\)6s have been calculated. The calculated energy levels are compared with experimental data available and show good agreement with it.